Comparison of Glomerular Filtration Rate Estimation from Serum Creatinine and Cystatin C in HNF1A-MODY and Other Types of Diabetes - Magdalena Szopa; Maria Kapusta; Bartlomiej Matejko; Tomasz Klupa; Teresa Koblik; Beata Kiec-Wilk; Maciej Borowiec; Maciej T. Malecki (Journal of Diabetes Research)
Introduction. We previously showed that in HNF1A-MODY the cystatin C-based glomerular filtration rate (GFR) estimate is higher than the creatinine-based estimate. Currently, we aimed to replicate this finding and verify its clinical significance. Methods. The study included 72 patients with HNF1A-MODY, 72 with GCK-MODY, 53 with type 1 diabetes (T1DM), 70 with type 2 diabetes (T2DM), and 65 controls. Serum creatinine and cystatin C levels were measured. GFR was calculated from creatinine and cystatin C using the CKD-EPI creatinine equation (eGRF-cr) and CKD-EPI cystatin C equation (eGFR-cys), respectively. Results. Cystatin C levels were lower (p<0.001) in the control (0.70±0.13 mg/L), HNF1A (0.75±0.21), and GCK (0.72±0.16 mg/L) groups in comparison to those with either T1DM (0.87±0.15 mg/L) or T2DM (0.9±0.23 mg/L). Moreover, eGFR-cys was higher than eGRF-cr in HNF1A-MODY, GCK-MODY, and the controls (p=0.004; p=0.003; p<0.0001). This corresponded to 8.9 mL/min/1.73 m2, 9.7 mL/min/1.73 m2, and 16.9 mL/min/1.73 m2 of difference. Additionally, T1DM patients had higher eGFR-cr than eGFR-cys (11.6 mL/min/1.73 m2; p=0.0004); no difference occurred in T2DM (p=0.91). Conclusions. We confirmed that eGFR-cys values in HNF1A-MODY patients are higher compared to eGFR-cr. Some other differences were also described in diabetic groups. However, none of them appears to be clinically relevant.